On the mechanism of cyclic crack propagation in AA2024 T3 alloy - Krkoska, M.; Paletti, L.; Alderliesten, R.C. (ICAF, 2023)
Fatigue cracks are known to be strongly affected by the type and parameters of the applied loading. The effect of the constant amplitude (CA) and underload (UL) loading was previously investigated on AA2024-T3 alloy in a large volume of research. It was observed that the morphologies of formed fracture surface striations, UL markers (surface ridges) and fissures were directly affected by the magnitude of applied loading cycles, and they are linked to the resulting crack depths and orientations of tilted local fracture surface planes. Despite the large amount of experimental evidences, a comprehensive understanding of the mechanisms governing the observed crack propagation behavior is still to be identified. Based on an experimental investigation using the so-called crack tip freezing approach, a novel mechanistic model, concerning the cyclic crack tip growth in ductile alloy and the formation of fracture surface features in the wake of progressing crack tip, is presented in this publication. The model covers the formation and the evolution of sharp V-shaped and blunted U-shaped profiles along the crack front, as a function of cyclic loading, and in relation to the crack depth and the local fracture plane tilt. The most significant aspect of the proposed mechanistic model is the incorporation of cyclic plastic deformation of the newly formed crack tip flanks as well as the deformation of previously formed fracture surface features positioned in the wake of the active crack tip. This cyclic, out of plane, deformation explains how the surface striations are shaped into convex profiles on both directly mating surfaces, which could not be previously explained. The developed model also describes the nucleation of the fracture surface fissures at the basis of newly formed crack tip flanks during the application of tensile load excursion and their further growth in the wake of the crack tip via the cyclic plastic deformation. The formation of the asymmetrically shaped crack tip profiles, plastic deformation in the crack wake and the formation of fracture surface features (typical of larger crack depths) are attributed in the model to the deviation of the propagating crack from the general fracture plane.